Subjective Well-Being Investigations: Domestic and Foreign Psychology (Хабаршы. Психология және социология сериясы, 2019)
Article presents the concept of subjective well- being. Starting from the philosophic point that describes the concept from the perspective of two forms: “hedonic” and “eudaimonic”. The necessity of studying subjective well- being and its actuality, which became a red flag that straightened in the wind through the centuries until nowadays. Why do human beings strive to obtain subjective well- being? What are the benefits for a person and society? To answer these questions paper refers to investigations made by popular organizations and scientists. The investigation history of subjective well- being concept, which is derived from theoretical and empirical studies. The theoretical studies represented by the ideas of E. From, Z. Freud, A.Adler, A.Maslow and other. The empirical studies that started in 1930s and used simple graphical scales or list of main categories. Later composed a list of factors of satisfaction that measured happiness. Then in 1990s scientific acknowledgement of happiness category was described. The meaning and matching of terminology: “happiness’ and “subjective well- being”. Finally, subjective well- being predictors and the concept in domestic and foreign psychology were presented.